Effective meetings 20 sure-fire tools - Parker, Glenn M. 1938- (HRD Press, 2009)
A successful meeting is not measured by starting on time, having a great agenda, getting everyone involved, or even serving healthy muffins. While all these factors are important...a great meeting is simply one that achieves its objectives--in other words, where a problem is solved, a decision is made, a plan is developed, a question answered, or some other specific outcome is accomplished. In Volume II of The Parker Team Series, Effective Meetings: 20 Sure-Fire Tools, author Glenn Parker will help you achieve your desired outcomes. This easy-to-read book will guarantee better meeting results, wh.
Includes bibliographical references (pages 67-68). - Print version record
Keywords: Business meetings -- Handbooks, manuals, etc; Réunions d'affaires; Guides, manuels, etc; BUSINESS & ECONOMICS; Business Communication; Meetings & Presentations; Business meetings; Handbooks and manuals